The Analysis of Social Media Use in Collaborative Learning on The Implementation of Online Knowledge Sharing to Improve Student Academic Performance - Nurul Janah; Puddy Prima; Aulia Puspaning Galih (Universitas Pendidikan Mandalika, 2024)
This research aims to analyze social media use in collaborative learning on the implementation of online knowledge sharing to maximally improve student academic performance. The research method used a survey with a quantitative approach. The research sample was taken by purposive sampling on diploma 3 and undergraduate students at several public and private universities in Java Island, Indonesia. As a result, 359 respondents filled out an online questionnaire distributed via a google form link. Data analysis using SEM PLS path analysis with SmartPLS program version 3.0. The results of this research stated that social media used in collaborative learning correlated with online knowledge sharing. The ease of sharing knowledge accelerates the dissemination of material delivered by teachers to students as a trigger for collecting questions and recommendations based on the student's point of view. Online knowledge sharing is related to student engagement, where students always update the knowledge that has been stored in their social media groups. Active student engagement will be assessed optimally by the teacher as a student reward so that academically the student's GPA increases, learning goals can be achieved, and students can contribute actively to spreading their knowledge through social media.